Rainfall distribution variability controls surface but not belowground litter decomposition in a semi-arid shrubland - Yulin Li; Li Cheng; Honglin Yang; Rui Zhang; Zhiying Ning (Frontiers in Plant Science)
IntroductionRainfall patterns are expected to become increasingly erratic as a result of global climate change, with more intense but less frequent rainfall events leading to an increased occurrence of drought events. This process may lead to significant declines in vegetation cover and subsequent increases in soil erosion, consequently accelerating the bury of detached litter by soil deposition and the mixture of residues from different plant species. Responses of litter decomposition to increasing rainfall variability in distribution and subsequent litter mixing or soil cover have scarcely received attention.MethodsTo fill this gap in our knowledge, we analyzed the influence of rainfall variability, soil cover, and litter mixing on shrub-species litter decomposition in a semi-arid shrubland. We explored the effects of redistributing the frequency and amount of precipitation on surface and belowground decomposition of litter from two separate or mixed predominant shrubs.ResultsDecomposition of belowground litter was consistently higher than that of surface litter over the entire field-incubation process. Mass loss significantly decreased in surface litter but not in belowground litter due to the lower frequency and larger amount of precipitation compared to the control treatment. Furthermore, exclusion of 30% precipitation had no significant effects on decomposition of either surface or belowground litter. We observed stronger synergistic effect for belowground litter mixture relative to surface litter mixture of the two shrubs, especially in the hotter months over the 5-month incubation.DiscussionThese findings support that rainfall variability in terms of distribution pattern rather than in the amount controls the litter decomposition on the soil surface in the semi-arid shrubland. Meanwhile, soil burial or litter mixing have greater effects on litter decomposition, individually or jointly. Together, our results highlight the need to consider rainfall distribution variability and incorporate soil-covering and litter-mixing as driving factors of organic matter turnover in drylands.